A importância da relação terapeuta - paciente na preparação e acompanhamento psicológico de pessoas que se submetem à cirurgia bariátrica - Catarino, Gabriela Nunes (2014)
This dissertation aimed, in general, analyze the action of the clinical psychologist in the preparation and psychological care of people undergoing bariatric surgery process. Specifically seeks to identify the elements that can interfere positively and / or negatively, in relation therapist - patient, analyze the resonances that therapeutic monitoring exercises on patients undergoing bariatric surgery. Sought to both the theoretical contributions about the body in Merleau Ponty and psychoanalysis Winnicott. Mainly addressed the relationship therapist - patient by Winnicott's approach and within the context of psychologists working with the theme of obesity. This is a qualitative study, whose participants seven clinical psychologists who develop activities in the field of bariatric surgery, both in the private and public sectors and two included patients aged 33 to 56 years, who underwent surgery and continue in psychological counseling. Semistructured interview used to psychologists and for both patients through a different starter question. The analysis of the narrative was taken from the thematic analysis, which identified themes related to the issue of professional practice and theoretical concepts used by psychologists, especially axes as the nature of the bond established relationship therapist and patient, the importance of family participation in the process and especially body image experienced by the patient before, during and after surgery. O care that the psychologist should have to take into account in its therapeutic relationship , the promotion of self-knowledge and understanding about a body experienced by the patient and therefore a body guy, not objectified ; constituted themselves as elements of fundamental importance , reminding us that policies accompanying attitudes are necessary but not sufficient for successful treatment. For these reasons, we point out that intrapsychic issues and the internal resources of the patient are sufficiently worked out, thus avoiding that the same replace the symptom of obesity by another symptom of compulsion.